2012
DOI: 10.1111/j.1745-4549.2011.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF BLANCHING AND VACUUM IMPREGNATION ON PHYSICOCHEMICAL AND SENSORY PROPERTIES OF INDIAN GOOSEBERRY (PHYLLANTHUS EMBLICAL.)

Abstract: Vacuum impregnation (VI) was employed for development of minimally processed Indian gooseberry. Blanching of the fruits at different temperatures (70-90C) and times (20-60 s) was studied, and the process combination of 90C and 60 s was chosen as the most suitable for inactivation of peroxidase (POD) and maintaining stability of the fruit's color. Also, increase in both blanching temperature and time could significantly (P Յ 0.05) reduce POD activity and result in blanched samples with higher yellowness. When t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Additionally, the increase in b* (yellowness) might be due to the thermal degradation of chlorophyll to pheophytin by overheating [ 24 ]. The increase in b* value was also obtained during MW-convective blanching of Pleurotus eryngii [ 22 ], and in Indian gooseberry [ 25 ].…”
Section: Resultsmentioning
confidence: 97%
“…Additionally, the increase in b* (yellowness) might be due to the thermal degradation of chlorophyll to pheophytin by overheating [ 24 ]. The increase in b* value was also obtained during MW-convective blanching of Pleurotus eryngii [ 22 ], and in Indian gooseberry [ 25 ].…”
Section: Resultsmentioning
confidence: 97%
“…Raj et al (2019) reported a 34% loss in vitamin C in amla juice after 20 min treatment at 60°C. Chinprahast et al (2013) applied blanching (1 min at 90°C) to the amla fruit followed by vacuum impregnation at 13.5 kPa for 10 min into a 50 °Brix osmotic solution made of honey and sucrose. The vacuum impregnated fruits were soaked in the same osmotic solution for 24 hr, and a 61% loss in vitamin C content was obtained.…”
Section: Vitamin Cmentioning
confidence: 99%
“…), also known as amla, is considered as a valuable fruit due to the vast content of polyphenols, tannins, minerals, and other phytochemicals. The antioxidant activity of this fruit is due to the presence of emblicanin A and B, which mainly include glucose, gallic, and ellagic acids (Chinprahast, Siripatrawan, Leerahawong, & Traiananwuttikul, 2013). Besides, it is the most abundant source of vitamin C within the citrus fruit family except Barbados cherry, and depending on the cultivars, it ranges from 480 to 550 mg/100 g of pulp (Hiwale, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Phyllanthus emblica (L), also known as embolic, is widely grown in the tropical and subtropical regions of Southern Asia. The fruits of embolic are used as food or medical ingredients in India and China (Chinprahast, Siripatrawan, Leerahawong, & Traiananwuttikul, ; Variya, Bakrania, & Patel, ), with many biological functions, such as antioxidant (Chatterjee, Bandyopadhyay, Ghosh, Ghosal, & Ray, ), chemopreventive (Krishnaveni & Mirunalini, ), and anti‐proliferative effects (Luo et al, ). Emblica fruits are rich in fiber, carbohydrate, vitamin C, amino acids, and phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%